2013
DOI: 10.1002/app.40172
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of high‐strength poly(ether ether ketone) films

Abstract: High-strength poly(ether ether ketone) (PEEK) films were prepared through melt extrusion followed by stretching. The tensile strength, orientation, and crystallization behaviors of PEEK films were characterized by universal testing machine, thermomechanical analysis, wide-angle X-ray diffraction, and differential scanning calorimetry. The results indicated that the tensile strength of PEEK films mainly depended on the stretching rate (m), stretching temperature (T), and stretching ratio (k L ). Moreover, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Later, the reduction of crystallinity in these PEEK/PEI blends, which is hindered completely, particularly at high cooling rates [12] when PEI content reaches 50% [5,12,17]. It is worth mentioning here the effect of crystallinity: it is well known that the best mechanical properties, thermal, and/or solvent resistance are not reached unless there is substantial crystallization [18][19][20][21]. Moreover, crystallinity plays an important role in the adhesion and mechanical properties of PEEK composites [22].…”
Section: Introductionmentioning
confidence: 99%
“…Later, the reduction of crystallinity in these PEEK/PEI blends, which is hindered completely, particularly at high cooling rates [12] when PEI content reaches 50% [5,12,17]. It is worth mentioning here the effect of crystallinity: it is well known that the best mechanical properties, thermal, and/or solvent resistance are not reached unless there is substantial crystallization [18][19][20][21]. Moreover, crystallinity plays an important role in the adhesion and mechanical properties of PEEK composites [22].…”
Section: Introductionmentioning
confidence: 99%
“…When subjecting the semi-crystalline PEEK beyond its glass transition temperature, the polymer chains begin to rearrange and hitherto initiate the crystallization process, which has been found to be highly effective at enhancing strength and stiffness. For instance, Li et al [ 15 ] revealed that, after keeping the neat PEEK film at 210 °C for a prolonged period of time, the overall crystallinity reached 29.7%, and the resultant strength reached 140.0 MPa, almost a 25.0% increase from the amorphous PEEK matrix. Crystallization also promotes electrical conductivity through expelling the conductive fillers to the boundaries of crystals, as dictated by the classic volume percolation theory [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that after total integration and subsequent cooling, PEI will remain unchanged [ 23 ], but the diffusion and infiltration of PEI chains into PEEK will inhibit the nucleation and growth of crystallites in the latter polymer. Reduced crystallinity has direct consequences on both the mechanical properties of the homogeneous polymer blend [ 24 , 25 ] and its ability to form a good bonding interface in PEEK-reinforced composite materials [ 26 , 27 ]. The multilayer polymer (MLP) stacking technique is an alternative strategy to handle these drawbacks.…”
Section: Introductionmentioning
confidence: 99%